Isospora belli infection associated with Chronic Cholecystitis and Sclerosing Cholangitis in Immuncompetent Host : A Case Report - Warnnissorn, Naree; Atisook, Kanit; Lohsirirwat, Darin; Ratanarapee, Samrerng; Laohaudomphan, Podjana; Netsakhon, Sarintorn (Siriraj Medical Journal, 2003)
Isospora belli (I. belli) is a spore-forming protozoa that primarily infects enterocyte. The clinical manifestation may very from asmptomatic to self-limited diarrhea in healthy persons. Rarely, in the normal hosts,5 chronic persistent or intermittent symptom may continue for many years.1,2 Treatment with cotrimoxazole is usually effective in both normal patients19 and patients with AIDS20,21 Nevertheless, relapse is common and is believed to be associated with the presence of extraintestinal infection.3,4,17 Few cases of extraintestinal I. belli infection have been documented in patients with AIDS,3-5 and one case in an immuncompetent patient.24 Â Â Â This report presents a unique case of isosporiasis in a 58-year-old anti-HIV negative Thai female suffering from chronic recurrent diarrhea due to I. belli, despite two episodes of complete 4-week cotrimoxazole and another course of nitazoxanide. Abdominal computer tomographic examination and ultrasonography identified sclerosing cholangitis and chronic cholecstitis. Histologic examination of the cholecystectomy specimen recovered schizonts and merozoites in the parasitophorous vacuoles located in gallbladder epithelium.